EFFECT OF CRYPTOCURRENCY ON THE SELECTED SECURITY MARKETS: A STUDY OF BITCOIN VOLATILITY USING VAR MODEL - Rewal, Megha; Singh, Parminder; Dara, Sonia (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In light of the growing interest among investors in the cryptocurrency market, this study investigates the relationship between Bitcoin and selected international stock markets, namely the Dow Jones Industrial Average, Euro Stoxx, FTSE 100, National Stock Exchange, and Shanghai Stock Exchange by utilizing statistical techniques such as regression analysis and the standard Vector Autoregressive (VAR) model, we aimed to detect any connections between Bitcoin and these stock markets. This empirical analysis reveals no significant autocorrelation between Bitcoin and the stock markets under consideration. This suggests that Bitcoin could potentially function as an asset offering hedging capabilities against risks associated with the selected stock markets. This research offers valuable insights into the dynamic relationship between cryptocurrency and financial markets